DAMPAK INDIKATOR MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM SEKTOR PERTANIAN - Satiri Satiri; Augustina Kurniasih (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
This research has objective to examine and analyze the effect of inflation rate, exchange rate (USD), oil price and interest rate to agriculture stock price index at Indonesia Stock Exchange (IDX). The research using monthly time series data for the period of January 2006 to December 2015. The study utilizes Autoregressive Distributed Lag model (ARDL) technique. The result shows in the short-run inflation rate, exchange rate (USD), oil price and interest rate simultaneously are having significant effect to agriculture stock price index. Partially, only oil price has positif and significant effect, while inflation rate, exchange rate (USD) and interest rate are not have significant effect to agriculture stock price index. While in the long-run no one of variables, inflation rate, exchange rate (USD), oil price and interest rate cointegarate to agriculture stock price index.